2014
DOI: 10.5005/jp-journals-10033-1210
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Vasectomy vs Laparoscopic Sterilization in Dogs: A Comparison of Two Techniques

Abstract: Twelve clinically healthy, adult male dogs randomly equally divided into two groups (I and II). Animals of both the groups received xylazine-ketamine anesthesia. Laparoscopic bilateral vasectomy was performed in group I, whereas in animals of group II in additition to vasectomy, spermatic artery-vein plexus were clipped with titanium clips at a distance of 1 to 2 cm. Insufflation of abdominal cavity was achieved by CO 2 (2 liter/minute) at 10 mm Hg pressure gradient. Clinical observations revealed no significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
(21 reference statements)
2
6
0
1
Order By: Relevance
“…Despite the low number of cases, none of the potential complications of the conventional technique were recorded with this laparoscopic technique. These findings are in agreement with results previously reported in other species with intra‐abdominal and extra‐abdominal DD, as dogs 26 and llamas and alpacas 36 . This approach can be an additional advantage in horses with previous orchitis or testicular trauma because in these situations, the DD isolation can be difficult with the conventional approach 14…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite the low number of cases, none of the potential complications of the conventional technique were recorded with this laparoscopic technique. These findings are in agreement with results previously reported in other species with intra‐abdominal and extra‐abdominal DD, as dogs 26 and llamas and alpacas 36 . This approach can be an additional advantage in horses with previous orchitis or testicular trauma because in these situations, the DD isolation can be difficult with the conventional approach 14…”
Section: Discussionsupporting
confidence: 93%
“…Reports of complications of vasectomy in veterinary medicine are limited, but our unpublished experience with conventional vasectomy in rams also presented a relative frequency of perioperative morbidity. Laparoscopic vasectomy has been described in human medicine 22–25 and also in some animal species showing that it is a simpler, safer and quicker procedure than the conventional technique, avoiding some complications of the open surgery 26 . However, there are no reports describing the laparoscopic vasectomy in the horse.…”
Section: Introductionmentioning
confidence: 99%
“…Alva et al (2006) reported that xylazineketamine induced oxidative stress without risking hepatic toxicity by increasing the level of plasmatic nitric oxide and change in acid-base balance and metabolic acidosis. The result of the present study was supported by the findings of Mahalingam et al (2014), as the authors reported that the xylazine -ketamine anaesthesia in dogs increased the lipid peroxidation. This was accompanied by enhanced antioxidant status as the superoxide dismutase and catalase which provided the first line of defence against the reactive oxygen species induced damages.…”
Section: Antioxidantssupporting
confidence: 88%
“…Detomidine did not influence the cortisol level in horses (Raekallio et al, 1991) and there was a significant reduction in cortisol level in horses after detomidine administration due to reduction in sympatho-adrenal activity (Raekallio et al, 1992). ketamine by its sympathotonic effect and activation of pituitary adrenocortical axis stimulated the plasma cortisol level (Bettschart-Wolfensberger et al, 1996 andMahalingam et al, 2014). Taylor and Watkins (1992) , Taylor et al (1995), Luna et al (1996) and Taylor et al (1998) found out a reduction in plasma cortisol concentration during detomidine, ketamine, guaifenesin anaesthesia.…”
Section: Plasma Cortisolmentioning
confidence: 99%
“…A vasectomia é o procedimento que consiste na interrupção da patência de ambos os ductos deferentes, podendo ser realizada em animais por diferentes técnicas a partir dos acessos convencional (Hedlund 2002, Kumar & Raj 2012 ou laparoscópico (Wildt et al 1981, Mahalingam et al 2009). Em cães, a aplicação de energia elétrica no ducto deferente seguida de sua secção pelo acesso minimamente invasivo tem demonstrado efetividade, comprovada pela produção de ejaculados azoospérmicos (Wildt et al 1981, Silva et al 1993.…”
Section: Introductionunclassified